The chronicles of Narnia - Lewis, C. S. (Clive Staples), 1898-1963 (Lewis, C. S. (Clive Staples), 1898-1963. Chronicles of Narnia (HarperCollins (Firm)), 2004)
Presents the unabridged text of C. S. Lewis's seven-part fantasy series in which a group of children walk into a magical realm called Narnia and find themselves in the midst of an ongoing battle between good and evil led by the Christlike lion king Aslan.